Who are environmental refugees? The political projections of the debate - Τσουμπάρης, Δημήτρης (The Greek Review of Social Research, 2010)
Since the1970s there has been a rich and often contradictory bibliography concerning the connection between environmental changes and human migration and the so called environmental refugees. The article both tries to present the relative public discourse from a critical viewpoint, as well as to clarify the term of environmental refugees and to examine its suitability. For this purpose, a case study analysis is being carried out which refers to situations of environmental destruction, degradation and expropriation. Further more, a criticism is being applied on the arguments concerning environmental security and its political extensions, by linking the subject with the implications of the developmental procedure and the criticism on North-South exploitative relations.